Calculations of the mass absorption cross sections for carbonaceous nanoparticles modeling soot. (October 2015) - García Fernández, C.; Picaud, S.; Devel, M.
Abstract: In this paper we use an atomistic model to calculate the mass specific absorption cross section coefficient (MAC) of carbonaceous particles of nanometer size. The carbonaceous particles are built numerically to reproduce most of the structural characteristics of typical primary nanoparticles that are agglomerated in soot emitted in the Troposphere from combustion sources. Our model is based on the knowledge of the atomic positions and polarizabilities inside the primary nanoparticles and is used to study the influence of these atomistic characteristics on the optical properties of these nanoparticles. The results indicate that the atomistic composition of the soot primary nanoparticles may have a sufficiently strong impact on the mass specific absorption cross section coefficient curves to allow detection of differences between nanoparticles by using UV–visible spectroscopic measurements, in a well-suited wavelength range, i.e., typically between 200 and 350 nm. In a more general way, our calculations show that MAC values as well as differences between MAC curves corresponding to different primary nanoparticles may strongly vary with wavelength. As a consequence, measurements at a given wavelength only are certainly not representative of the absorption properties of these nanoparticles and thus should be considered with caution. Moreover, our approach clearly shows significant differences with classical macroscopic electromagnetic theory when calculating the optical properties of realistic primary soot nanoparticles that, in fact, cannot be considered as homogeneous spherical particles due to the presence of defects in their atomistic structure. Abstract : Highlights: We calculate the MAC curves of carbonaceous particles. Relation between atomistic characteristics and MAC curves is characterized. We show that MAC curves depend on the atomistic composition of the nanoparticles Difference between nanoparticles may be characterized by spectroscopic measurements. Differences between MAC curves may strongly vary with wavelength.